Electrochemical preparation of bimetallic pt-ru supported catalysts using organic additives - Sieben, Juan; Duarte, Marta; Mayer, Carlos (Revista Ciências Exatas, 2009)
The simultaneous codeposition of Pt and Ru on carbon materials was carried out potentiostatically at -0.5 V using H2PtCl6 and RuCl3 aqueous solutions in presence of different organic additives: 1) ethylene glycol, 2) ethanol, 3) formic acid, 4) sodium citrate, 5) sodium tartrate and 6) Na2H2EDTA. The electrodeposition process was influenced thermodynamically and kinetically by the stabilizers. SEM and AFM analysis of the electrodes showed that the particle size and the active surface area were notably influenced by the stabilizing agents. The dissimilar behaviour of the stabilizing agents may be associated with the following effects:(1) the capability of the stabilizing agent to complex the metal ions, (2) the specific adsorption of organic molecules that inhibits the particle growth, and (3) the reduction capability of the organic compounds. The catalytic activity of the electrodes synthesized with the different additives in the methanol oxidation reaction obtaining the following decreasing order: citrate > tartrate > ethanol > Na2H2EDTA > ethylene glycol > formic acid > without stabilizer. This comportment can be related to the differences in the active surface area, particle size and superficial structure of the metallic deposit.